Liquid crystal polyarylester fiber and preparation method thereof

Through prepolymerization of specific proportioning monomers and catalysts and solid phase polycondensation reactions, liquid crystal polyaryl fibers are prepared, which solves the safety hazards caused by creep on offshore cables, and achieves performance improvements of high strength and low creep rate. Suitable for high-demand applications such as marine special cables.

CN119121439APending Publication Date: 2024-12-13ZHEJIANG YONGCHUAN JUJIA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310623.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In special environments where deep water high pressure, seawater corrosion, alternation of high and low temperatures, and periodic repeated changes in tensile forces, offshore cables are prone to cable breakage events due to creep, which poses high safety hazards.

Method used

Prepolymerization and solid phase polycondensation reaction are used to prepare liquid crystal polyaryl fibers by spraying the spinning assembly to insulate the fiber wires, air-cooling, drafting and heat treatment, thereby enhancing the fibers Creep resistance.

Benefits of technology

The obtained liquid crystal polyaryl fiber has high strength, low creep rate, and creep rate is less than 0.002198%/month, which significantly improves the safety of the cable and is suitable for offshore special cables and other high-demand applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005050579490000061
    Figure BDA0005050579490000061
  • Figure BDA0005050579490000111
    Figure BDA0005050579490000111
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a preparation method of liquid crystal polyarylate fibers. The preparation method specifically comprises the following steps: mixing monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3, 6-dihydroxyacridine and isophthalic acid with an acylation reagent and a catalyst according to a specific ratio to obtain a reaction mixture; carrying out prepolymerization reaction on the reaction mixture to obtain a prepolymer; and performing solid-phase polycondensation reaction on the prepolymer in an inert gas atmosphere to obtain the liquid crystal polyarylester, heating and extruding the liquid crystal polyarylester, then supplying the liquid crystal polyarylester to a spinning assembly, spraying fibers through the spinning assembly, and carrying out heat preservation, air cooling, drafting and shaping, and yarn separation and rolling on the fibers to obtain nascent fibers; the tensile strength of the finished product fiber reaches 3.0 GPa or above, the tensile modulus of the finished product fiber reaches 90 GPa or above, the creep rate of the finished product fiber is lower than 0.002198% / month, and the finished product fiber is used for the marine special cable, so that the safety of the cable can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a liquid crystal polyarylate fiber and a preparation method thereof. Background Art

[0002] At present, with the development of deep-sea resources, cables need to help marine engineering equipment stay in the operating sea area for a long time. They need to withstand special environments such as deep-water high pressure, seawater corrosion, high and low temperature alternation, and periodic changes in tensile force, which also puts higher performance requirements on them. Usually cables include steel wire cables and synthetic fiber cables. Because steel wire ropes are heavy under the same strength and are not resistant to seawater corrosion, they are gradually being replaced by synthetic fiber cables in the field of marine engineering. In addition to being much lighter than steel cables and having greatly improved flexibility and corrosion resistance, users have also found that using synthetic fiber cables is safer than using steel wire ropes. For example, the rebound of synthetic fiber mooring cables when broken is much smaller than that of steel wire mooring cables, and it is not easy to cause personal injury; in addition, synthetic fiber cables are also more convenient to use and store.

[0003] Synthetic fiber cables mainly include cables made of polyester, nylon, high-strength polyethylene, aramid and other fibers. The research on the performance of synthetic fibers for these cables is mostly focused on strength, modulus, corrosion resistance, wear resistance and other aspects. In fact, during offshore operations, the cables need to have sufficient displacement stroke to meet the high elongation requirements of the cables. In addition to bearing the long-term marine environmental load, such long-distance cables will also be swung by the wind and waves on the sea surface. During these processes, the fiber cables will creep or even creep and break. If not given enough attention, cable breakage is likely to occur, resulting in serious consequences.

[0004] Liquid crystal polyarylate fiber is a high-performance fiber with better performance than polyester, nylon, high-strength polyethylene, aramid and other fibers. It has excellent properties such as high strength and modulus, acid and alkali corrosion resistance, radiation resistance, high temperature resistance and creep resistance. In recent years, it has been used in special offshore cables. In order to further reduce the safety hazards caused by creep of cables, the inventors have done a lot of research on how to further improve the creep resistance of liquid crystal polyarylate fiber. Summary of the invention

[0005] The purpose of the present invention is to provide a liquid crystal polyarylate fiber with excellent comprehensive performance, especially improved creep resistance, in view of the above technical problems. The fiber can be used for special offshore cables to further improve the safety of the cables.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing liquid crystal polyarylate fiber, which comprises the following preparation steps:

[0007] S1: mixing monomers p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid with an acylating agent and a catalyst to obtain a reaction mixture; wherein, in terms of molar percentage, the molar percentages of the four monomers are as follows: p-hydroxybenzoic acid 26-55 mol%, 5-hydroxy-7-azaindole-2-carboxylic acid 25-40 mol%, 3,6-dihydroxyacridine 10-17 mol%, isophthalic acid 10-17 mol%;

[0008] S2: subjecting the reaction mixture to a prepolymerization reaction to obtain a prepolymer;

[0009] S3: Under an inert gas atmosphere, subjecting the prepolymer to a solid phase polycondensation reaction to obtain a liquid crystal polyarylate;

[0010] S4: heating and extruding the liquid crystal polyarylate, and supplying the liquid crystal polyarylate to a spinning assembly, spraying fiber filaments through the spinning assembly, and performing heat preservation, air cooling, drawing and shaping, and filament separation and winding on the fiber filaments to obtain nascent fibers;

[0011] S5: heat-treating the spun fibers to obtain finished fibers.

[0012] Preferably, in step S1, the molar ratio of the monomer 3,6-dihydroxyacridine to isophthalic acid is 1:1.

[0013] Preferably, in step S1, the catalyst is N-vinylimidazole, and the added amount is 200-400 ppm of the total weight of the four monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine and isophthalic acid.

[0014] Preferably, the acylating agent in step S1 includes at least one of acetic anhydride, propionic anhydride, butyric anhydride, valeric anhydride and maleic anhydride, and the added amount is 1.1-1.8 times the total molar number of hydroxyl groups in the four monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine and isophthalic acid.

[0015] Preferably, the liquid crystal polyarylate obtained in step S3 is heated to a temperature of 30°C above the melting point and a shear rate of 1000 sec. -1 The melt index is 100-150cm 3 / 10min.

[0016] Preferably, in step S4, the liquid crystal polyarylate is heated to 300-340° C. and then extruded.

[0017] Preferably, the insulation temperature in step S4 is 290-320° C., and the speed of the drawing and shaping is 800-1000 m / min.

[0018] Preferably, the heat treatment temperature in step S5 is 290-330° C. and the time is 12-24 hours.

[0019] The second object of the present invention is to provide a liquid crystal polyarylate fiber, which is prepared by the above-mentioned preparation method of liquid crystal polyarylate fiber.

[0020] The beneficial technical effects of the present invention are:

[0021] The liquid crystal polyarylate fiber obtained by the present invention using a specific ratio of polymerization monomers, catalysts and preparation processes not only has good mechanical properties, a tensile strength of more than 3.0 GPa, a tensile modulus of more than 90 GPa, but also has excellent creep resistance, a creep rate of less than 0.002198% / month. It is used in special offshore cables to improve the safety of the cables. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0023] An embodiment of the present invention provides a liquid crystal polyarylate fiber, which is obtained by the following preparation method:

[0024] S1: mixing monomers p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid with an acylating agent and a catalyst to obtain a reaction mixture; wherein, in terms of molar percentage, the molar percentages of the four monomers are as follows: p-hydroxybenzoic acid 26-55 mol%, 5-hydroxy-7-azaindole-2-carboxylic acid 25-40 mol%, 3,6-dihydroxyacridine 10-17 mol%, isophthalic acid 10-17 mol%;

[0025] S2: subjecting the reaction mixture to a prepolymerization reaction to obtain a prepolymer;

[0026] S3: Under an inert gas atmosphere, subjecting the prepolymer to a solid phase polycondensation reaction to obtain a liquid crystal polyarylate;

[0027] S4: heating and extruding the liquid crystal polyarylate, and supplying the liquid crystal polyarylate to a spinning assembly, spraying fiber filaments through the spinning assembly, and performing heat preservation, air cooling, drawing and shaping, and filament separation and winding on the fiber filaments to obtain nascent fibers;

[0028] S5: heat-treating the spun fibers to obtain finished fibers.

[0029] Optionally, in step S1, the molar ratio of the monomer 3,6-dihydroxyacridine to isophthalic acid is 1:1.

[0030] Optionally, the reaction mixture in step S2 is subjected to a prepolymerization reaction to obtain a prepolymer, comprising: keeping the reaction mixture at 120-140°C for 1-3h, then heating it to 290-330°C and keeping it for 1-3h, then filling a Hastelloy kettle with 0.5-1.0MPa inert gas, discharging the reaction product through a discharge valve with a diameter of 2-4mm and 8-10 holes, crushing it, passing it through a 20-30 mesh sieve, and drying it at 110-120°C for 1-2h to obtain the prepolymer.

[0031] Optionally, in step S3, the temperature of the solid phase polycondensation reaction is 290-330° C., and the time is 12-36 hours.

[0032] Optionally, in step S1, the catalyst is N-vinylimidazole, and the added amount is 200-400 ppm of the total weight of the four monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine and isophthalic acid.

[0033] Optionally, the acylating agent in step S1 includes at least one of acetic anhydride, propionic anhydride, butyric anhydride, valeric anhydride and maleic anhydride, and the added amount is 1.1-1.8 times the total molar number of hydroxyl groups in the four monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine and isophthalic acid.

[0034] Optionally, the liquid crystal polyarylate obtained in step S3 is heated at a melting point of +30°C and a shear rate of 1000 sec -1 The melt index is 100-150cm 3 / 10min.

[0035] Optionally, in step S4, the liquid crystal polyarylate is heated to 300-340° C. and then extruded.

[0036] Optionally, the insulation temperature in step S4 is 290-320° C., and the speed of the drawing and shaping is 800-1000 m / min.

[0037] Optionally, the heat treatment temperature in step S5 is 290-330° C. and the time is 12-24 hours.

[0038] The monomer ratios in the embodiments of the present invention are shown in Table (1).

[0039] Table (1) Monomer ratios in Examples 1-4

[0040]

[0041] Example 1

[0042] According to the 1# monomer ratio, p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid are mixed with acylating agents acetic anhydride, propionic anhydride, butyric anhydride and valeric anhydride, maleic anhydride accounting for 1.5 times the total molar number of hydroxyl groups in the four monomers, and catalyst N-vinyl imidazole accounting for 300 ppm of the total weight of the four monomers to obtain a reaction mixture.

[0043] The reaction mixture was kept at 130°C for 2 hours, then heated to 310°C and kept for 2 hours, after which 0.6 MPa of inert gas was charged into the Hastelloy kettle, and the reaction product was discharged through a discharge valve with a diameter of 2 mm and 10 holes, crushed, passed through a 30-mesh sieve, and dried at 110°C for 2 hours to obtain the prepolymer; in an inert gas atmosphere, the prepolymer was subjected to a solid phase polycondensation reaction at 320°C for 30 hours to obtain a liquid crystal polyarylate; the melting point was determined to be 307°C by DSC, and the melt flow rate instrument XNR-400DT was used to determine the melting point at +30°C and a shear rate of 1000 sec -1 The melt index is 130cm 3 / 10min.

[0044] The liquid crystal polyarylate is heated to 320°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept at 310°C, air-cooled to room temperature, stretched and shaped at a speed of 900 m / min, and then divided and wound to obtain spun fibers; the spun fibers are heat-treated at 310°C for 18 hours to obtain finished fibers.

[0045] Example 2

[0046] According to the 2# monomer ratio, p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid, acylating agents acetic anhydride, propionic anhydride, butyric anhydride and valeric anhydride, maleic anhydride accounting for 1.2 times the total molar number of hydroxyl groups in the four monomers, and catalyst N-vinyl imidazole accounting for 250 ppm of the total weight of the four monomers are mixed to obtain a reaction mixture.

[0047] The reaction mixture was kept at 120°C for 2 hours, then heated to 300°C and kept for 2 hours, after which 0.8 MPa of inert gas was charged into the Hastelloy kettle, and the reaction product was discharged through a discharge valve with a diameter of 4 mm and 8 holes, crushed, passed through a 20-mesh sieve, and dried at 120°C for 1 hour to obtain the prepolymer; in an inert gas atmosphere, the prepolymer was subjected to a solid phase polycondensation reaction at 300°C for 24 hours to obtain a liquid crystal polyarylate; the melting point was determined to be 316°C by DSC, and the melt flow rate meter XNR-400DT was used to determine the melting point at +30°C and a shear rate of 1000 sec. -1The melt index is 110cm 3 / 10min.

[0048] The liquid crystal polyarylate is heated to 320°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept at 310°C, air-cooled to room temperature, stretched and shaped at a speed of 800 m / min, and then divided and wound to obtain spun fibers; the spun fibers are heat treated at 310°C for 15 hours to obtain finished fibers.

[0049] Example 3

[0050] According to the 3# monomer ratio, p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid, acylating agents acetic anhydride, propionic anhydride, butyric anhydride and valeric anhydride, maleic anhydride accounting for 1.8 times the total molar number of hydroxyl groups in the four monomers, and catalyst N-vinyl imidazole accounting for 400 ppm of the total weight of the four monomers are mixed to obtain a reaction mixture.

[0051] The reaction mixture was kept at 140°C for 1 hour, then heated to 330°C and kept at this temperature for 1 hour, after which 1.0 MPa of inert gas was charged into the Hastelloy kettle, and the reaction product was discharged through a discharge valve with a diameter of 2 mm and 10 holes, crushed, passed through a 30-mesh sieve, and dried at 120°C for 2 hours to obtain the prepolymer; in an inert gas atmosphere, the prepolymer was subjected to a solid phase polycondensation reaction at 330°C for 36 hours to obtain a liquid crystal polyarylate; the melting point thereof was determined to be 320°C by DSC, and the melt flow rate meter XNR-400DT was used to determine the melting point at +30°C and a shear rate of 1000 sec. -1 The melt index is 100cm 3 / 10min.

[0052] The liquid crystal polyarylate is heated to 340°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept at 320°C, air-cooled to room temperature, stretched and shaped at a speed of 1000 m / min, and then divided and wound to obtain spun fibers; the spun fibers are heat treated at 330°C for 24 hours to obtain finished fibers.

[0053] Example 4

[0054] According to the 4# monomer ratio, p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid are mixed with acylating agents acetic anhydride, propionic anhydride, butyric anhydride and valeric anhydride, maleic anhydride accounting for 1.1 times the total molar number of hydroxyl groups in the four monomers, and catalyst N-vinyl imidazole accounting for 200 ppm of the total weight of the four monomers to obtain a reaction mixture.

[0055] The reaction mixture was kept at 120°C for 3 hours, then heated to 290°C and kept for 3 hours, after which 0.5 MPa of inert gas was charged into the Hastelloy kettle, and the reaction product was discharged through a discharge valve with a diameter of 4 mm and 8 holes, crushed, passed through a 20-mesh sieve, and dried at 110°C for 2 hours to obtain the prepolymer; in an inert gas atmosphere, the prepolymer was subjected to a solid phase polycondensation reaction at 290°C for 12 hours to obtain a liquid crystal polyarylate; the melting point was determined to be 300°C by DSC, and the melt flow rate meter XNR-400DT was used to determine the melting point at +30°C and a shear rate of 1000 sec -1 The melt index is 150cm 3 / 10min.

[0056] The liquid crystal polyarylate is heated to 300°C and then extruded, supplied to a spinning assembly, through which fiber filaments are ejected, the fiber filaments are kept at 290°C, air-cooled to room temperature, stretched and shaped at a speed of 800 m / min, and then divided and wound to obtain spun fibers; the spun fibers are heat treated at 290°C for 12 hours to obtain finished fibers.

[0057] Comparative Example 1

[0058] The only difference from Example 1 is that the monomer p-hydroxybenzoic acid is replaced by an equal molar amount of 5-hydroxy-7-azaindole-2-carboxylic acid; the melting point of the liquid crystal polyarylate is 293°C as determined by DSC, and the melt flow rate is measured by a melt flow rate meter XNR-400DT at a temperature of 30°C above the melting point and a shear rate of 1000 sec. -1 The melt index is 161cm 3 / 10min.

[0059] Comparative Example 2

[0060] The only difference from Example 1 is that the monomer 5-hydroxy-7-azaindole-2-carboxylic acid is replaced by an equal molar amount of p-hydroxybenzoic acid. The melting point of the liquid crystal polyarylate is 334°C as determined by DSC. The melt flow rate meter XNR-400DT is used to measure the melting point at +30°C and a shear rate of 1000 sec. -1 The melt index is 89cm 3 / 10min.

[0061] Comparative Example 3

[0062] The only difference from Example 1 is that 3,6-dihydroxyacridine is replaced by an equal molar amount of biphenol. The melting point of the liquid crystal polyarylate is 303°C as determined by DSC, and the melt flow rate is measured by a melt flow rate meter XNR-400DT at a temperature of 30°C above the melting point and a shear rate of 1000 sec. -1The melt index is 140cm 3 / 10min.

[0063] Comparative Example 4

[0064] The only difference from Example 1 is that the monomer isophthalic acid is replaced by an equal molar amount of terephthalic acid. The melting point of the liquid crystal polyarylate is 312°C as determined by DSC, and the melt flow rate is measured by a melt flow rate meter XNR-400DT at a temperature of 30°C above the melting point and a shear rate of 1000 sec. -1 The melt index is 124cm 3 / 10min.

[0065] Comparative Example 5

[0066] The only difference from Example 1 is that the catalyst N-vinylimidazole is replaced by an equal amount of potassium acetate.

[0067] Comparative Example 6

[0068] The only difference from Example 1 is that the as-spun fibers are not subjected to heat treatment.

[0069] The relevant performance testing method of the liquid crystal polyarylate fiber of the present invention is as follows:

[0070] (1) Tensile strength and modulus: measured at 20±2°C and 60±3% in accordance with GB / T 19975-2005.

[0071] (2) Creep resistance: The creep resistance of the fiber is measured manually by the suspension method, that is, one end of the fiber is fixed, and a certain weight or weight is hung on the other end. At the same time, a ruler is set next to the fiber to measure its elongation over time and then convert it into a creep rate. Usually, the fiber is often used after being combined with a matrix to form a composite material, so it is considered to directly test the creep resistance of the fiber dipped yarn. Specifically, a fiber bundle with a length of 1.5m is cut, uniformly impregnated in epoxy resin, and then cured at room temperature for 24h to form a dipped yarn. Then, one end of the dipped yarn is fixed on the test device table, and a weight of 10g is hung on the other end. A ruler is hung parallel to each sample. After standing for one week, its initial length A1 is measured. After hanging for 10 months, the length A2 is measured again, and its creep rate is calculated as (A2-A1 / 10A1)×100%.

[0072] The results of Examples 1-4 and Comparative Examples 1-6 measured using the above performance testing method are shown in Table (2).

[0073] Table (2): Performance test results of Examples 1-4 and Comparative Examples 1-6

[0074]

[0075] According to the data in Table (2), the liquid crystal polyarylate fiber obtained by adopting the overall technical solution of the present invention not only has good mechanical properties, with a tensile strength of more than 3.0 GPa and a tensile modulus of more than 90 GPa, but also has excellent creep resistance, with a creep rate of less than 0.002198% / month. It can be used for special offshore cables to improve the safety of the cables. In addition, it can also be used to make climbing ropes, space landing ropes, cables for aircraft to suspend heavy objects, high-altitude balloon slings, etc.

[0076] The above-mentioned implementation mode is only a preferred technical solution of the present invention. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and working principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing liquid crystal polyarylate fiber, characterized in that: The preparation method comprises the following steps: S1: mixing monomers p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, isophthalic acid with an acylating agent and a catalyst to obtain a reaction mixture; wherein, in terms of molar percentage, the molar percentages of the four monomers are as follows: p-hydroxybenzoic acid 26-55 mol%, 5-hydroxy-7-azaindole-2-carboxylic acid 25-40 mol%, 3,6-dihydroxyacridine 10-17 mol%, isophthalic acid 10-17 mol%; S2: subjecting the reaction mixture to a prepolymerization reaction to obtain a prepolymer; S3: Under an inert gas atmosphere, subjecting the prepolymer to a solid phase polycondensation reaction to obtain a liquid crystal polyarylate; S4: heating and extruding the liquid crystal polyarylate, and supplying the liquid crystal polyarylate to a spinning assembly, spraying fiber filaments through the spinning assembly, and performing heat preservation, air cooling, drawing and shaping, and filament separation and winding on the fiber filaments to obtain nascent fibers; S5: heat-treating the spun fibers to obtain finished fibers.

2. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: In the step S1, the molar ratio of the monomer 3,6-dihydroxyacridine to isophthalic acid is 1:

1.

3. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: In step S1, the catalyst is N-vinylimidazole, and the added amount is 200-400 ppm of the total weight of the four monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine, and isophthalic acid.

4. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: In step S1, the acylating agent includes at least one of acetic anhydride, propionic anhydride, butyric anhydride, valeric anhydride and maleic anhydride, and the added amount is 1.1-1.8 times the total molar number of hydroxyl groups in the four monomers of p-hydroxybenzoic acid, 5-hydroxy-7-azaindole-2-carboxylic acid, 3,6-dihydroxyacridine and isophthalic acid.

5. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: The liquid crystal polyarylate obtained in step S3 is heated to a temperature of 30°C above the melting point and a shear rate of 1000 sec -1 The melt index is 100-150cm 3 / 10min.

6. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: In the step S4, the liquid crystal polyarylate is heated to 300-340° C. and then extruded.

7. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: The insulation temperature in step S4 is 290-320° C., and the drawing and shaping speed is 800-1000 m / min.

8. The method for preparing liquid crystal polyarylate fiber according to claim 1, characterized in that: The heat treatment temperature in step S5 is 290-330° C. and the time is 12-24 hours.

9. A liquid crystal polyarylate fiber, characterized in that: The liquid crystal polyarylate fiber is prepared by the preparation method of any one of claims 1 to 8.